Approaches to the Bargaining Problem Before and After the Theory of Games: A Critical Discussion of Zeuthen's, Hicks', and Nash's Theories - Harsanyi, John C. (Econometrica, 1956)
John C. Harsanyi, Approaches to the Bargaining Problem Before and After the Theory of Games: A Critical Discussion of Zeuthen's, Hicks', and Nash's Theories, Econometrica, Vol. 24, No. 2 (Apr., 1956), pp. 144-157